Synthesis, Characterization and Conductivity Studies of Tetraphenylstibonium Halides and Trihalides - Khan, Abdullah; K. Azad, Abul; Hussain, Izhar; Uddin, Fahim (Asian Journal of Chemistry, 2010)
A series of tetraphenylstibonium halides and tetraphenylstibonium trihalides compounds of type Ph4SbX (X = F, Cl, Br, I) and Ph4SbX3 (X3 = Br3, IBr2, ICl2) have been synthesized as crystalline solids. The electrolytic conductivity measurement in acetonitrile show that Ph4SbF is very weak, Ph4SbCl and Ph4SbBr are weak but Ph4SbI is a strong electrolyte. All of the trihalides show strong electrotytic conductivity. The calculation of molar conductivity supports the experimental results. The conductometric titrations studies of Ph4SbCl with ICl, Ph4SbBr with Br2 and IBr indicate that the trihalides Ph4SbX3 are formed readily in acetonitrile solution.